The Changing Landscape of Hydrocarbon Feedstocks for Chemical Production: Implications for Catalysis: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
A decade ago, the U.S. chemical industry was in decline. Of the more than 40 chemical manufacturing plants being built worldwide in the mid-2000s with more than 1 billion in capitalization, none were under construction in the United States. Today, as a result of abundant domestic supplies of affordable natural gas and natural gas liquids resulting from the dramatic rise in shale gas production, the U.S. chemical industry has gone from the world's highest-cost producer in 2005 to among the lowest-cost producers today. The low cost and increased supply of natural gas and natural gas liquids provides an opportunity to discover and develop new catalysts and processes to enable the direct conversion of natural gas and natural gas liquids into value-added chemicals with a lower carbon footprint. The economic implications of developing advanced technologies to utilize and process natural gas and natural gas liquids for chemical production could be significant, as commodity, intermediate, and fine chemicals represent a higher-economic-value use of shale gas compared with its use as a fuel. To better understand the opportunities for catalysis research in an era of shifting feedstocks for chemical production and to identify the gaps in the current research portfolio, the National Academies of Sciences, Engineering, and Medicine conducted an interactive, multidisciplinary workshop in March 2016. The goal of this workshop was to identify advances in catalysis that can enable the United States to fully realize the potential of the shale gas revolution for the U.S. chemical industry and, as a result, to help target the efforts of U.S. researchers and funding agencies on those areas of science and technology development that are most critical to achieving these advances. This publication summarizes the presentations and discussions from the workshop.

Leveraging the Future Research and Development Ecosystem for the Intelligence Community—Understanding the International Aspect of the Landscape: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
On June 9, 2021, the Intelligence Community Studies Board of the National Academies of Sciences, Engineering, and Medicine convened a virtual workshop on behalf of the Office of the Director of National Intelligence. This unclassified workshop was the second of two data-gathering workshops.

Exploring the Current Landscape of Consumer Genomics: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Consumer genomics, encompassing both direct-to-consumer applications (i.e., genetic testing that is accessed by a consumer directly from a commercial company apart from a health care provider) and consumer-driven genetic testing (i.e., genetic testing ordered by a health care provider in response to an informed patient request), has evolved considerably over the past decade, moving from more personal utility-focused applications outside of traditional health care to interfacing with clinical care in nontraditional ways. As consumer genomics has increasingly intersected with clinical applications, discussions have arisen around the need to demonstrate clinical and analytical validity and clinical utility due to the potential for misinterpretation by consumers. Clinical readiness and interest for this information have presented educational and training challenges for providers. At the same time, consumer genomics has emerged as a potentially innovative mechanism for thinking about health literacy and engaging participants in their health and health care. To explore the current landscape of consumer genomics and the implications for how genetic test information is used or may be used in research and clinical care, the Roundtable on Genomics and Precision Health of the National Academies of Sciences, Engineering, and Medicine hosted a public workshop on October 29, 2019, in Washington, DC. Discussions included such topics as the diversity of participant populations, the impact of consumer genomics on health literacy and engagement, knowledge gaps related to the use of consumer genomics in clinical care, and regulatory and health policy issues such as data privacy and security. A broad array of stakeholders took part in the workshop, including genomics and consumer genomics experts, epidemiologists, health disparities researchers, clinicians, users of consumer genomics research applications, representatives from patient advocacy groups, payers, bioethicists, regulators, and policy makers. This publication summarizes the presentations and discussion of the workshop.

Health Literacy and Older Adults: Reshaping the Landscape: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
Adults age 65 and older make up the fastest-growing segment of the U.S. population. At the same time, the complexity of health care delivery continues to grow, creating challenges that are magnified for older adults, given that age is one of the highest correlates of low health literacy. This creates a shared obligation between health care and the health care team to use the principles, tools, and practices of health literacy so that patients and families of older adults can more easily navigate discussions related to chronic disease, polypharmacy, long-term care, palliative care, insurance complexities, the social determinants of health, and other factors that create challenges for older adults, particularly among underserved populations nationwide. To gain a better understanding of the health communication challenges among older adults and their professional and family caregivers and how those challenges affect the care older adults receive, the National Academies of Sciences, Engineering, and Medicine2019s Roundtable on Health Literacy convened a 1-day public workshop featuring presentations and discussions that examined the effect of low health literacy on the health of older adults. This publication summarizes the presentations and discussions from the workshop.

Community Colleges in the Evolving STEM Education Landscape: Summary of a Summit - National Academy of Engineering; National Research Council (The National Academies Press, 2012)
The National Research Council (NRC) and National Academy of Engineering (NAE) have released a new report, Community Colleges in the Evolving STEM Education Landscape: Summary of a Summit. Based on a national summit that was supported by the National Science Foundation and organized by the NRC and the NAE, the report highlights the importance of community colleges, especially in emerging areas of STEM (Sciene, Technology, Engineering, and Mathematics) and preparation of the STEM workforce. Community colleges are also essential in accommodating growing numbers of students and in retraining displaced workers in skills needed in the new economy. Community Colleges in the Evolving STEM Education Landscape: Summary of a Summit looks at the changing and evolving relationships between community colleges and four-year institutions, with a focus on partnerships and articulation processes that can facilitate student success in STEM; expanding participation of students from historically underrepresented populations in undergraduate STEM education; and how subjects, such as mathematics, can serve as gateways or barriers to college completion.

Physician-Assisted Death: Scanning the Landscape: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
The question of whether and under what circumstances terminally ill patients should be able to access life-ending medications with the aid of a physician is receiving increasing attention as a matter of public opinion and of public policy. Ethicists, clinicians, patients, and their families debate whether physician-assisted death ought to be a legal option for patients. While public opinion is divided and public policy debates include moral, ethical, and policy considerations, a demand for physician-assisted death persists among some patients, and the inconsistent legal terrain leaves a number of questions and challenges for health care providers to navigate when presented with patients considering or requesting physician-assisted death. To discuss what is known and not known empirically about the practice of physician-assisted death, the National Academies of Sciences, Engineering, and Medicine convened a 2-day workshop in Washington, DC, on February 12201313, 2018. This publication summarizes the presentations and discussions from the workshop.

Addressing Bioterrorism in a Changing Scientific and Security Context: Abbreviated Version of a Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
On November 29, 2022, the National Academies of Sciences, Engineering, and Medicine convened a classified workshop to explore the current policy landscape and outstanding needs for countering bioterrorism within the changing threat and risk contexts. This workshop 2013 in brief summarizes the outcomes of the workshop discussion.

Evolving the Culture of Science and Training in Neuroscience to Meet a Changing World: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
Recent events, including the COVID-19 pandemic and the collective awakening around issues related to racial justice, diversity, and inclusion, have underscored the challenges facing neuroscience and neuroscience training. To address these challenges, the Forum on Neuroscience and Nervous System Disorders of the National Academies of Sciences, Engineering, and Medicine convened a series of virtual workshops on neuroscience training with the goal of reconsidering how we think about neuroscience training in a rapidly changing world. On February 22, 2021, the fifth and final workshop in this series, titled Evolving the Culture of Science and Training in Neuroscience to Meet a Changing World, brought together stakeholders from across the neuroscience ecosystem to discuss how the culture of science and scientific training can become more inclusive, balanced, and adaptive to changing times. This final workshop expanded on many issues raised in previous workshops, including the importance of mental health and well-being in academic research; how to resist the legacy of white supremacy and support diversity in academia; and how to redefine what success means for neuroscientists in both academic and non-academic settings. This publication summarizes the discussions that occurred at the workshop.

Integrating Landscape Approaches and Multi-Resource Analysis into Natural Resource Management: Summary of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
The responsible management of natural resources for present-day needs and future generations requires integrated approaches that are place-based, embrace systems thinking, and incorporate the social, economic, and environmental considerations of sustainability. Landscape-scale analysis takes this holistic view by focusing on the spatial scales most appropriate for the resource types and values being managed. Landscape-scale analysis involves assessing landscape features in relation to a group of influencing factors such as land use change, hydrologic changes or other disturbances, topography, and historical vegetation conditions. As such, different types of data and multiple disciplines may be required for landscape analysis, depending on the question of interest and scale of analysis. Multi-resource analysis (MRA) is an approach to landscape-scale analysis that integrates information among multiple natural resources, including ecosystem services, and is designed to evaluate impacts and tradeoffs between development and conservation at landscape scales to inform public resource managers. This approach implicitly addresses social, economic, and ecological functional relationships; for example, actions to realize the benefits of one type of natural resource (e.g., minerals, oil, and gas) may influence behavior and potential benefits related to other types of natural resources (e.g., recreational opportunities). In June 2015, the National Academies of Sciences, Engineering, and Medicine convened a workshop on using landscape-based approaches and MRA to better inform federal decision making for the sustainable management of natural resources. Participants discussed knowledge gaps and priority areas for research and presentations of case studies of approaches that have been used to effectively integrate landscape-based approaches and MRA into practice. This report summarizes the presentations and discussions from the workshop.

Navigating the Energy Transition in the Gulf of Mexico: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Today, with a changing climate putting pressure on communities and ecosystems worldwide, goals for a carbon-neutral economy mean that renewable and low-carbon energy sources are being presented as solutions. While these cleaner energy sources have the potential to reduce risk to the environment and bring energy security closer to a reality, questions remain about the stability of the energy supply chain, the ability to meet energy demand reliably, and the best ways to produce fair and equitable outcomes in an energy transition. To serve as a catalyst for developing new insights and coordination around the energy transition, the Gulf Research Program at the National Academies of Sciences, Engineering, and Medicine convened a 2-day workshop in Washington, DC, called Navigating the Energy Transition in the Gulf of Mexico. Based around two scenarios in the year 2050 - one in which a carbon neutral economy is achieved and another in which robust dependence on fossil fuels remains - this serious gaming event stimulated the sharing of ideas, concerns, and cascading impacts from participants across academia, industry, government, and Gulf communities. This publication summarizes the activities, presentations, and discussion of the workshop.

Enhancing Federal Clean Energy Innovation: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine
A widespread and rapid transition to a low-carbon energy system by 2050 is essential to keep pace with ambitious policy goals and avoid the worst consequences of climate change. Innovation is necessary to lower costs and improve performance of existing technologies and to develop new clean energy options that address challenges in harder-to-decarbonize sectors. To examine means by which the U.S. federal government can rise to this challenge, the National Academies of Sciences, Engineering, and Medicine hosted a virtual workshop series \

The Role of Research and Technology in the Changing Ocean Economy: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Oceans have long been a frontier of opportunity for exploration, scientific understanding, commerce, and trade for the United States. The transformative technologies of the fourth industrial revolution - artificial intelligence, machine learning, robotics, Internet of Things, biotechnology, advanced materials - are expected to recondition traditional ocean-based industries and enable the growth of new markets prioritizing sustainability. At the nexus of unprecedented environmental change and rapid technology innovation, how should the United States position itself as a leader in the global ocean economy? On February 4 and 5, 2020, the Government-University-Industry Research Roundtable convened experts to discuss the importance of cross-sector collaboration and the opportunities for U.S. leadership in the context of a changing ocean and a changing ocean economy. This publication highlights the presentation and discussion of the workshop.

Energy Reduction at U.S. Air Force Facilities Using Industrial Processes: A Workshop Summary - National Research Council (The National Academies Press, 2013)
The Department of Defense (DoD) is the largest consumer of energy in the federal government. In turn, the U.S. Air Force is the largest consumer of energy in the DoD, with a total annual energy expenditure of around 10 billion. Approximately 84 percent of Air Force energy use involves liquid fuel consumed in aviation whereas approximately 12 percent is energy (primarily electricity) used in facilities on the ground. This workshop was concerned primarily with opportunities to reduce energy consumption within Air Force facilities that employ energy intensive industrial processes2014for example, assembly\/disassembly, painting, metal working, and operation of radar facilities2014such as those that occur in the maintenance depots and testing facilities. Air Force efforts to reduce energy consumption are driven largely by external goals and mandates derived from Congressional legislation and executive orders. To date, these goals and mandates have targeted the energy used at the building or facility level rather than in specific industrial processes. In response to a request from the Deputy Assistant Secretary of the Air Force for Energy and the Deputy Assistant Secretary of the Air Force for Science, Technology, and Engineering, the National Research Council, under the auspices of the Air Force Studies Board, formed the Committee on Energy Reduction at U.S. Air Force Facilities Using Industrial Processes: A Workshop. The terms of reference called for a committee to plan and convene one 3 day public workshop to discuss: (1) what are the current industrial processes that are least efficient and most cost ineffective? (2) what are best practices in comparable facilities for comparable processes to achieve energy efficiency? (3) what are the potential applications for the best practices to be found in comparable facilities for comparable processes to achieve energy efficiency? (4) what are constraints and considerations that might limit applicability to Air Force facilities and processes over the next ten year implementation time frame? (5) what are the costs and paybacks from implementation of the best practices? (6) what will be a proposed resulting scheme of priorities for study and implementation of the identified best practices? (7) what does a holistic representation of energy and water consumption look like within operations and maintenance?

Selected Directed Energy Research and Development for U.S. Air Force Aircraft Applications: A Workshop Summary - National Research Council (The National Academies Press, 2013)
The U. S. Air force currently invests significantly in science and technology for directed-energy weapon (DEW) systems. Key elements of this investment include high-energy lasers and high-power microwaves. Other DEW research and development efforts include: optical beam control for high-energy lasers; vulnerability and lethality assessments; and advanced non-conventional and innovative weapons. Selected Directed Energy Research and Development for U.S. Air Force Aircraft Applications is the summary of three workshop sessions convened between February and April, 2013 by the Air Force Studies Board of the National Academies' National Research Council. Representatives from the Air Force science and technology community and DEW experts from the U.S. Army, U.S. Navy, Office of the Secretary of Defense, and the Defense Advanced Research Projects Agency presented and discussed threats that DEW capabilities might defend against and assessments of foreign progress in DEW. This report examines the current status of DEW capabilities both in the U.S. and abroad, and considers future applications of DEW systems.

Toward a Transformational Africa-U.S. STEM University Initiative: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
STEM (science, technology, engineering, and mathematics) plays a key role in accelerating economic growth and developing innovative solutions to pressing challenges facing the African continent. Over the past few decades, much work has been done to develop university systems in African countries in recognition of the role that high-caliber teaching and research in STEM fields play in economic development. African universities and their governments have made many of these gains through partnering across countries and sectors. Often, however, these efforts are based on individual connections and do not lead to long-term change. Inspired by STEM's potential to tackle African and global challenges, a group of academic leaders has come together to explore a synergistic approach to transform African institutions of higher education and increase the global engagement of U.S. institutions. They developed an initial vision for a next-generation Africa-U.S. STEM initiative that would take place for at least 10 years, with funds of at least 10 million annually from governments, the private sector, philanthropies, and other organizations. To obtain input from stakeholders on how such an initiative could develop, the group held a virtual workshop March 14-16, 2022, convened by the National Academies of Sciences, Engineering, and Medicine. This publication summarizes the presentations and discussions of the workshop.

Pathways to an Equitable and Just Energy Transition: Principles, Best Practices, and Inclusive Stakeholder Engagement: Proceedings of a Workshop - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
While technologies are clearly instrumental in transitioning away from fossil fuel-based energy and toward a decarbonized economy, decisions about which technologies are prioritized, how they are implemented, and the policies that drive these changes will have profound effects on people and communities, with important implications for equity, jobs, environmental and energy justice, health, and more. The National Academies of Sciences, Engineering, and Medicine Committee on Accelerating Decarbonization in the United States: Technology, Policy, and Societal Dimensions was tasked with assessing the broad range of technological, policy, and societal dimensions of decarbonizing the U.S. economy. The committee produced a 2021 report that provides the U.S. government with a roadmap of equitable and robust decarbonization policies. The next report of the committee will address the broader range of policy actors who play a role in equitable energy transition. To inform its deliberations, the committee hosted a 1-day workshop on July 26, 2022 to discuss critical issues of equity and justice during the energy transition. The goal of the workshop, titled Pathways to an Equitable and Just Transition: Principles, Best Practices, and Inclusive Stakeholder Engagement, was to move beyond energy technologies and elicit ideas and insights to inform the development of principles, best practices, and actionable recommendations for a broad range of policy actors and stakeholders in order to fully operationalize equity, justice, and inclusion. This publication summarizes the presentations and discussion of the workshop.

Frontiers in Thermal Transport and Energy Conversion: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Thermal transport and energy conversion has remained an active field for at least 200 years, with numerous opportunities for discoveries and new applications. Recently, experiments have advanced researchers' understanding of basic physics, and how new discoveries might translate into applications in energy, materials, quantum technologies, and other areas. The National Academies convened a workshop on April 11, 2019 to identify and assess the frontier of current research in the field of thermal transport and energy conversion. Discussions involved topics related to thermal transport and quasi-particle hydrodynamics, thermal transport beyond the quasiparticle paradigm, the thermal hall effect from neutral spin excitations in frustrated quantum magnets, quantization of the thermal hall conductivity at small hall angles, and thermal spin transport, including spin-seebeck and magnon drag effects. These topics were strategically selected with the goal of uncovering key challenges, opportunities, and issues in order to guide future efforts and investments to advance the field. This publication offers a condensed summary of the discussions and presentations from the workshop, which was unclassified and open to the public.

Developing Human Capital to Support U.S. Innovation Capacity: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Domestic and international competition for STEM talent is driving institutions across the research and innovation landscape to consider new policies and partnerships for building and managing STEM knowledge and skills. New levels of investment in human capital to increase U.S. innovation capacity and competitiveness will require coordination and collaboration among academic institutions, workforce development programs, labor organizations, companies, and funders of research and education. On October 18-19, 2022, the Government-University-Industry Research Roundtable convened a workshop for its membership and invited guests to consider the strategic priority of human capital investment in preparing the future workforce and supporting national innovation capacity. The workshop discussions examined the state of U.S. workforce preparation and considered trends in supply and demand for human capital to meet the needs of a transforming research enterprise. This publication summarizes the presentation and discussion of the workshop.

China-U.S. Scientific Engagement: Strengthening Collaborations for Sustainability and Biodiversity: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
Scientists in China and in the United States have addressed key topics related to sustainability in both formal and informal collaborations for many years. To further this engagement, the U.S. National Academies of Sciences, Engineering, and Medicine and the Chinese Academy of Sciences are convening a series of three workshops. Each workshop will examine the state of sustainability research and practices; identify priority areas for scientific collaboration on specific challenges; and discuss opportunities for advancing policy actions and the potential for new technology development and deployment in China and the United States. The first workshop took place July 27 to July 29 2022 and focused on sustainability and biodiversity as an important area of sustainability research and practices. This publication summarizes the presentations and discussion of the workshop.

Countering Terrorism: Biological Agents, Transportation Networks, and Energy Systems: Summary of a U.S.-Russian Workshop - National Academy of Sciences (The National Academies Press, 2009)
This book presents the proceedings of the fourth U.S.-Russian interacademy workshop on the general theme of countering terrorism, which was held in Moscow in March 2007. The fourth in a series, this volume continues to explore topics related to urban terrorism, but with a new emphasis on potential attacks involving biological agents, transportation networks, and energy systems. The other books in the series include: High Impact Terrorism: Proceedings of a Russian-American Workshop (2002) Terrorism: Reducing Vulnerabilities and Improving Responses: U.S.-Russian Workshop Proceedings (2004) Countering Urban Terrorism in Russia and the United States: Proceedings of a Workshop (2006)